The Mediator complex kinase module is necessary for fructose regulation of liver glycogen levels through induction of glucose-6-phosphatase catalytic subunit (G6pc) - Dou Yeon Youn; Alus M. Xiaoli; Haihong Zong; Junichi Okada; Li Liu; Jacob Pessin; Jeffrey E. Pessin; Fajun Yang (Elsevier, 2021)
Objective: Liver glycogen levels are dynamic and highly regulated by nutrient availability as the levels decrease during fasting and are restored during the feeding cycle. However, feeding in the presence of fructose in water suppresses glycogen accumulation in the liver by upregulating the expression of the glucose-6-phosphatase catalytic subunit (G6pc) gene, although the exact mechanism is unknown. We generated liver-specific knockout MED13 mice that lacked the transcriptional Mediator complex kinase module to examine its effect on the transcriptional activation of inducible target gene expression, such as the ChREBP- and FOXO1-dependent control of the G6pc gene promoter. Methods: The relative changes in liver expression of lipogenic and gluconeogenic genes as well as glycogen levels were examined in response to feeding standard low-fat laboratory chow supplemented with water or water containing sucrose or fructose in control (Med13fl/fl) and liver-specific MED13 knockout (MED13-LKO) mice. Results: Although MED13 deficiency had no significant effect on constitutive gene expression, all the dietary inducible gene transcripts were significantly reduced despite the unchanged insulin sensitivity in the MED13-LKO mice compared to that in the control mice. G6pc gene transcription displayed the most significant difference between the Med13 fl/fl and MED13-LKO mice, particularly when fed fructose. Following fasting that depleted liver glycogen, feeding induced the restoration of glycogen levels except in the presence of fructose. MED13 deficiency rescued the glycogen accumulation defect in the presence of fructose. This resulted from the suppression of G6pc expression and thus G6PC enzymatic activity.Among two transcriptional factors that regulate G6pc gene expression, FOXO1 binding to the G6pc promoter was not affected, whereas ChREBP binding was dramatically reduced in MED13-LKO hepatocytes. In addition, there was a marked suppression of FOXO1 and ChREBP-β transcriptional activities in MED13-LKO hepatocytes. Conclusions: Taken together, our data suggest that the kinase module of the Mediator complex is necessary for the transcriptional activation of metabolic genes such as G6pc and has an important role in regulating glycogen levels in the liver through altering transcription factor binding and activity at the G6pc promoter.